1983
DOI: 10.1113/jphysiol.1983.sp014660
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hypoxic pulmonary vasoconstriction and arterial oxygen tension in the intact dog.

Abstract: SUMMARY1. The relationship between the magnitude ofhypoxic pulmonary vasoconstriction (h.p.v.) and arterial oxygen tension (Pa02) has been studied in intact anaesthetized dogs.2. Radioactive 133Xe was infused continuously into the inferior vena cava. A tracheal divider made it possible to vary the inspired gas composition to each lung independently. With constant ventilation the '33Xe in the mixed expired gas from each lung was proportional to the blood flow to that lung.3. Unilateral ventilation of the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…It is interesting to note that oxygen want and carbon dioxide ... call forth a contraction of the lung vessels, thereby increasing the blood flow to better aerated lung areas, which leads to improved conditions for the utilization of alveolar air." Consistent with this proposal, numerous reports subsequently demonstrated that ventilating a sublobar lung region (653,1012), lung lobe (103,141,143,422,1192,1645,1761,1764,1852), or an individual lung (355,380,415,421,473,717,719,778,1192,1435,1579,1823,1825,1999) with an hypoxic gas mixture (F I O 2 ϭ 0 -13%) while ventilating the remaining lung with a normoxic or hyperoxic gas mixture decreased blood flow in the hypoxic region by 20 -100%. Since total flow was unaltered, these decreases represent diversion of flow from hypoxic to nonhypoxic lung due to HPV in hypoxic lung.…”
Section: Overviewmentioning
confidence: 63%
See 1 more Smart Citation
“…It is interesting to note that oxygen want and carbon dioxide ... call forth a contraction of the lung vessels, thereby increasing the blood flow to better aerated lung areas, which leads to improved conditions for the utilization of alveolar air." Consistent with this proposal, numerous reports subsequently demonstrated that ventilating a sublobar lung region (653,1012), lung lobe (103,141,143,422,1192,1645,1761,1764,1852), or an individual lung (355,380,415,421,473,717,719,778,1192,1435,1579,1823,1825,1999) with an hypoxic gas mixture (F I O 2 ϭ 0 -13%) while ventilating the remaining lung with a normoxic or hyperoxic gas mixture decreased blood flow in the hypoxic region by 20 -100%. Since total flow was unaltered, these decreases represent diversion of flow from hypoxic to nonhypoxic lung due to HPV in hypoxic lung.…”
Section: Overviewmentioning
confidence: 63%
“…Vasodilators including NO or PGI 2 added to gas mixtures ventilating the hypoxic regions (205,553) and dobutamine (1435), PGE 1 (1012), SNP (355, 778), or TNG (355) infused intravenously increased regional Q and/or venous admixture and decreased P a O 2 in lungs of dogs, pigs, and sheep. In contrast, agents given to enhance HPV, such as almitrine at doses Ͻ5 g·kg Ϫ1 ·min Ϫ1 (295, 1359, 1882), indomethacin (719,1823,1825), L-NAME (553, 1825), or L-NAME ϩ indomethacin (1825) decreased regional Q and/or increased P a O 2 in lungs of dogs, pigs, and rabbits.…”
Section: Assessment Of the Role Of Hpv In V A /Q Matchingmentioning
confidence: 99%
“…This principle, also known as the von Euler-Liljestrand mechanism, thereby optimises gas exchange at the blood-air interface [1,2]. Impairment of this mechanism during pathological situations in lung or systemic disease (for example, adult respiratory distress syndrome [3] or hepatopulmonary syndrome [4]) or during anaesthesia [5], may result in insufficient oxygenation of arterial blood and poor oxygen supply to the body.…”
mentioning
confidence: 99%
“…11,12 It is an adaptive vasomotor response to alveolar hypoxia, which redistributes blood to optimally ventilated lung segments by an active process of vasoconstriction, particularly involving the small muscular pulmonary arteries. Mild impairment of FEV 1 /FVC and FEF 25%-75% might relate to hypoxic pulmonary vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%